Assessment of psychological distress in end stage renal disease: is it spirituality related? - Fradelos, Evangelos C.; Alikari, Victoria; Tsaras, Konstantinos; Papathanasiou, Ioanna V.; Tzavella, Foteini; Papagiannis, Dimitrios; Zyga, Sofia (Medicine and Pharmacy Reports, 2021)
Abstract Introduction. Patients undergoing hemodialysis (HD) are faced with bearing this burden and report poor mental health. Spirituality can be a key factor in managing these problems among HD patients. Aim. This cross-sectional study aimed at exploring possible factors that are associated with psychological distress among HD patients and testing its relation to spirituality. Methods. HD patients were recruited from six dialysis units in Greece. Psychological distress was assessed using the scale Symptom Check List 90-R and spirituality using the Facit Sp-12 questionnaire. In addition, a special design questionnaire regarding demographic, social, and clinical characteristic was administrated. Results. According to the results, factors such age, gender, marital status and area of residence are associated with psychological distress, while dimensions of spirituality such Meaning in Life and Peace can have a positive influence on psychological distress. Conclusion. This study highlights the vital role of spirituality, which can act as a mechanism for managing stressful situations. In particular, this study highlights the positive effect of the meaning and purpose of life, as well as the role of peace and harmony.